Problemy rozwoju dróg powiatowych na przykładzie województwa lubelskiego - Myna, Artur (Powiats' Roads Development Problems on the Example of the Lublin Voivodeship, 2008)
The aim of the paper is presentation of barriers of roads development funding on the example of the powiats and county towns of the Lublin voivodship. The results of the study indicate that powiat and county town authorities concentrate on modernization of roads instead of building new ones. In 2000-2003, investment expenditure in transport of the powiats of the Lublin voivodship were over twofold lower than road subsidies obtained by them. Powiats spent most of the road subsidies on current exploitation of roads or funding other tasks than transport. County towns financed investment expenditure from external sources, such as repayable revenue. As a result, the debt of county towns considerably increased, although it did not exceed the statutory limits.(original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 3, s. 479-489